THE RELATIONSHIP BETWEEN FIRST, SECOND, AND THIRD PLACE SATISFACTION AND MENTAL HEALTH AMONG YOUNG ADULT WORKERS IN GREATER JAKARTA - Nadella, Audiza
Human life involves three primary settings: the first place (residence), the second place (workplace), and the third place. The conditions of the built environment, specifically the first, second, and third place, can affect individual satisfaction with these locations. Perceptions within these environments – namely, the first, second, and third place – can impact individual satisfaction and contribute to mental health outcomes. Currently, Indonesia’s population is dominated by productive groups – namely, the Millennial and Z Generation cohorts. These generations are vulnerable to mental health disorders. The objective of ths study is to examine the influence of the first, second, and third places (residence, workplace, and other social environment) on mental health, focusing on Gen Z and millennials in Greater Jakarta. Additionally, the study examines factors significantly influencing satisfaction within these places. This study utilizes a mixed-method sequential exploratory design. Initially, qualitative research is conducted, followed by confirmation in the subsequent quantitative phase. Data collection involves distributing online questionnaires via social networks, employing non-random and snowball sampling techniques.The analytical approaches encompass both conventional content analysis and directed content analysis during the initial research phase. In the subsequent phase, factor analysis and multivariate regression techniques are employed. The results from the first phase identify distinct categories of place quality that significantly impact satisfaction. Specifically, the first place is characterized by eight categories: ‘unit housing characteristics’, ‘location and accessibility’, ‘social environment’, ‘surrounding environment quality’, ‘facilities and amenities’, ‘housing management’, ‘utilities’, and ‘ownership status’. The second place comprises 13 categories: ‘office design and layout’, ‘room quality’, social environment’, ‘location and environment facilities’, ‘facilities and infrastructure’, ‘visual comfort’, ‘cleanliness and maintenance’, ‘acoustic quality’, ‘personal control’, ‘thermal comfort', 'building quality’, ‘illumination’, and ‘air quality’. The third place includes 10 categories: ‘recreational aspects’, ‘place quality’, ‘location and accessibility’, ‘social aspects’, ‘design features', ‘environmental ambience’, ‘public facilities’, ‘activities’, ‘cost’, and ‘management’. The results of the second-phase research reveal a relationship between satisfaction with the first and second place and mental health. However, no significant association is found between satisfaction with the third place and mental health. Furthermore, the study identifies two dimensions of first place quality (environmental dimension and design quality) that influence satisfaction; three dimension of second-place quality (spatial design, maintenance, and social dimensions) affecting satisfaction, and three dimensions of third-place quality (place quality, environmental factors, and facility characteristics) significantly impact satisfaction.